P127 Hospice respite: Moving forwards not backwards. (1st October 2013) - Day, Lindsay; Gregory, Amanda; Read, Paul
Abstract : Anecdotal evidence suggested that respite provision at an independent hospice was dominated by patients with neurological or non cancer diagnoses and that a small number of patients had a disproportionately large amount of respite admissions compared to those with a cancer diagnosis. A service review was undertaken to investigate whether the provision of respite was equitable across all patient groups. A retrospective review of notes identified patients referred for a respite admission within a 12 month period. The individual patient files were scrutinised to obtain relevant data for analysis, including the level of specialist palliative care received prior to admission. Respite provision appeared to attract a fairly equal number of referrals across cancer and non-cancer groups, although the latter were more likely to access multiple episodes of respite. Of the non-cancer groups, those with a neurological condition represented the highest proportion of patients accessing respite. It is likely that these results are due to the longer term, unpredictable nature of non-cancer conditions resulting in increased carer burden and subsequent need for respite care . The care needs of non-cancer patients suggest that a specialist palliative care centre is not necessarily required for respite. It is recommended that: alternative models of respite care are explored for these patients such as nursing home or an increase in home-care packages; the hospice continues to support local nursing home providers in order to facilitate the provision of high quality respite care within our community; during a patient's first respite admission, an assessment is undertaken to determine the most suitable place for ongoing respite care; respite guidelines to be adjusted to reflect a specified number of admissions per year.